Implementasi Nilai Nilai Pancasila Dalam Membangun Karakter Pendidikan Di Indonesia - Sri Yunita; Mirza Khairaz Rambe; Suryanizega; Nia Afriska Sinaga; Zuhrini Adawiyah Ahmadi Hasibuan; Rani Holy Tresia Lumbantobing (Jurnal Nirta : Inovasi Multidisiplin, 2026)
Character education in Indonesia currently faces serious challenges in the form of moral degradation and the negative influence of globalization, which is eroding national identity. This study aims to analyze strategies for implementing Pancasila values ​​in the national education system as an effort to strengthen students' character. The research method used was descriptive qualitative with a library research approach, which examined various current educational policies, including the Pancasila Student Profile program in the Independent Curriculum. The results indicate that internalization of Pancasila values ​​cannot be achieved solely through cognitive transformation in the classroom but must be integrated through school culture, teacher role models, and project-based co-curricular activities. The research findings indicate that consistent implementation of the values ​​of divinity, humanity, unity, democracy, and justice can increase social cohesion and tolerance in students amidst diversity. The conclusions of this study emphasize that successful Pancasila-based character development requires collective synergy between educational institutions, the family environment, and government policies that are adaptive to changing times. Keywords: Pancasila, Character Education, Pancasila Student Profile, Value Implementation, Indonesia.